Pengelolaan Sampah Plastik Dalam Mewujudkan Desa Bersih Dan Sehat (Studi Kasus Desa Pulau Telo) - kkn_com; Khairunnisa, Khairunnisa; Tricahyono, Nor Salim; Ageman, Bagus; Yanti, Rena Nur; Safitri, Rya; Ikrimah, Ikrimah; Hikmah, Nur; Triana, Sonia; Mahfudz, Muhammad Alwi (Lembaga Dongan Dosen, 2023)
The condition of the people in Pulau Telo village often dispose of household waste in the river which causes waste which is increasing every day and year, the need for awareness from the community not to litter because it will reduce the beauty of the village and discomfort in the community environment. Community efforts must be able to manage waste by recycling waste to produce waste that has value. the cooperation needed in dealing with waste by means of the village head holding socialization on waste recycling so that people can use plastic waste to become waste that has a price. This type of research is qualitative-descriptive which aims to describe the condition of the environmental cleanliness of the Kapuas River in Telo Island Village and the surrounding environment and the awareness of the surrounding community about river cleanliness.The result of community service activities is that by utilizing plastic as an attraction for the community to be able to manage waste as creative materials such as ecobricks.